Respostas

2014-01-07T10:51:07-02:00
Sec²x = 4

( \frac{1}{cosx} )² = 4

 \frac{1}{ (cosx)^{2} } = 4

cos²x*4 = 1

cosx² =  \frac{1}{4}

cosx =  \sqrt{ \frac{1}{4} }

cosx =  \frac{1}{2} (como x está no 3º quadrante então o seno e o cosseno são
negativos)

cosx = -\frac{1}{2}


sen²x+cos²x = 1

sen²x+ ( \frac{1}{2}) ^{2} = 1

sen²x = 1 -  \frac{1}{4}

sen²x =  \frac{3}{4}

senx =  \sqrt{ \frac{3}{4} }

senx =  \frac{ \sqrt{3} }{2}

senx = - \frac{ \sqrt{3} }{2}


tgx =  \frac{senx}{cosx}

tgx =  -\frac{ \sqrt{3} }{ \frac{2}{- \frac{1}{2} } }

tgx =  \frac{2 \sqrt{3} }{2}

tgx = √3

B) x = 60 
3 5 3